Mental health, gender, and drug court completion - Gray, Alison R. (American journal of criminal justice, 2005)
Drug-involved offenders report high rates of mental health problems that can negatively impact criminal justice outcomes. Yet, relatively little attention has been given to the mental health issues of drug court offenders. Therefore, this study examined 449 participants in a Delaware drug court and investigated relationships between mental health, gender, and program completion. Bivariate results indicated that gender was related to both mental health status and completion status. Multivariate findings revealed that two indicators of mental health, depression and being prescribed drugs for a psychological or emotional problem, were significant predictors of drug court completion. Policy implications include assessing the mental health status of all drug court participants at program entry so that services can be provided which aim to improve offender health and increase the likelihood of successful program outcomes. Drug courts must better meet the needs of participants with co-occurring disorders if they are to remain an effective and viable criminal justice intervention.